1986
DOI: 10.1042/bj2330119
|View full text |Cite
|
Sign up to set email alerts
|

Chymopapain A. Purification and investigation by covalent chromatography and characterization by two-protonic-state reactivity-probe kinetics, steady-state kinetics and resonance Raman spectroscopy of some dithioacyl derivatives

Abstract: Chymopapain A was isolated from the dried latex of papaya (Carica papaya) by ion-exchange chromatography followed by covalent chromatography by thiol-disulphide interchange. The latter procedure was used to produce fully active enzyme containing one essential thiol group per molecule of protein, to establish that the chymopapain A molecule contains, in addition, one non-essential thiol group per molecule and to recalculate the literature value of epsilon 280 for the enzyme as 36 000 M-1 X cm -1. The Michaelis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The isolation procedures for most of the enzymes have been described previously: papain (Baines & Brocklehurst, 1979); actinidin (Brocklehurst et al, 1981b); papaya proteinase Ql (papaya peptidase A) (Baines & Brocklehurst, 1982;Brocklehurst & Salih, 1983); bovine spleen cathepsin B (Willenbrock & Brocklehurst, 1984); chymopapain A (Baines et al, 1986). Chymopapains B1-B3 were isolated from the dried latex of Carica papaya supplied by Powell & Scholefield, Liverpool, U.K., by ion-exchange chromatography as described for the enzymes of fresh non-fruit papaya latex by Brocklehurst et al (1985b).…”
Section: Materials and Methods Enzymesmentioning
confidence: 99%
“…The isolation procedures for most of the enzymes have been described previously: papain (Baines & Brocklehurst, 1979); actinidin (Brocklehurst et al, 1981b); papaya proteinase Ql (papaya peptidase A) (Baines & Brocklehurst, 1982;Brocklehurst & Salih, 1983); bovine spleen cathepsin B (Willenbrock & Brocklehurst, 1984); chymopapain A (Baines et al, 1986). Chymopapains B1-B3 were isolated from the dried latex of Carica papaya supplied by Powell & Scholefield, Liverpool, U.K., by ion-exchange chromatography as described for the enzymes of fresh non-fruit papaya latex by Brocklehurst et al (1985b).…”
Section: Materials and Methods Enzymesmentioning
confidence: 99%
“…On the other hand, very little structural information for the other two enzymes is available in the literature. The fraction known as chymopapain has been separated into several forms by cationexchange chromatography [4][5][6]; two main components, named chymopapains A and B, seem to be different in the reactivity of the thiol group at the active site [7]. However, Buttle & Barrett [4] have shown that the multiple forms of chymopapain are immunologically identical, suggesting that the chromatographic multiplicity of this proteinase is the result of post-translational modifications [8].…”
Section: Introductionmentioning
confidence: 99%